A Case Based Approach to Clinical Genetics of Thoracic Aortic Aneurysm/Dissection. (25th May 2016) - Giusti, Betti; Nistri, Stefano; Sticchi, Elena; De Cario, Rosina; Abbate, Rosanna; Gensini, Gian Franco; Pepe, Guglielmina
Abstract : Thoracic aortic aneurysm/dissection (TAAD) is a potential lethal condition with a rising incidence. This condition may occur sporadically; nevertheless, it displays familial clustering in >20% of the cases. Family history confers a six- to twentyfold increased risk of TAAD and has to be considered in the identification and evaluation of patients needing an adequate clinical follow-up. Familial TAAD recognizes a number of potential etiologies with a significant genetic heterogeneity, in either syndromic or nonsyndromic forms of the manifestation. The clinical impact and the management of patients with TAAD differ according to the syndromic and nonsyndromic forms of the manifestation. The clinical management of TAAD patients varies, depending on the different forms. Starting from the description of patient history, in this paper, we summarized the state of the art concerning assessment of clinical/genetic profile and therapeutic management of TAAD patients.